Screening of undiagnosed hyperglycaemia in the dental setting: The DiabetRisk study. A field trial. (21st December 2020) - Montero, Eduardo; Matesanz, Paula; Nobili, Antonio; Luis Herrera‐Pombo, José; Sanz, Mariano; Guerrero, Adrián; Bujaldón, Antonio; Herrera, David
Abstract: Aim: To evaluate the efficacy of different screening protocols for undiagnosed hyperglycaemia in a Research Network of Dental Clinics coordinated by the Spanish Society of Periodontology (SEPA). Material and Methods: A total of 1143 patients were included in the study. Participants filled a questionnaire considering diabetes risk factors (FINDRISC) and received a periodontal screening examination. Patients with a slightly elevated score according to the Findrisc (≥7), received a point‐of‐care HbA1c and were eventually referred to their physician for confirmatory diagnosis. Receiver Operating Characteristic (ROC) curves were used to assess the performance of various predictive models with confirmed hyperglycaemia as outcome. Results: From this population, 97 (8.5%) were finally diagnosed of diabetes ( n  = 28; 2.5%) or prediabetes ( n  = 69; 6.0%). When only including the results from the FINDRISC questionnaire, the model reported an area under the curve (AUC) of 0.866 (95% confidence interval ‐ CI [0.833; 0.900]). This model significantly improved when a basic periodontal examination (EPB Code; AUC = 0.876; 95% CI [0.845: 0.906]; p  = .042) or a point‐of‐care HbA1c were added (AUC = 0.961; 95% CI [0.941; 0.980]; p  < .001). Conclusions: The tested protocol, combining the FINDRISC questionnaire and a point‐of‐care HbA1c, showed to be feasible when carried out in a dental clinic setting and was efficient to identify subjects with undiagnosed diabetes or prediabetes.